Evaluation of skeletal maturation using mandibular third molar development in Indian adolescents - Mehta, Nishit (J Forensic Dent Sci, 2016)
OBJECTIVE: This study was done with the following objectives: to estimate dental maturity using the Demirjian Index (DI) for the mandibular third molar; to investigate the relationship between dental maturity and skeletal maturity among growing patients; to evaluate the use of the mandibular third molar as an adjunctive tool for adolescent growth assessment in combination with the cervical vertebrae; to evaluate the clinical value of the third molar as a growth evaluation index. MATERIALS AND METHODS: Samples were derived from panoramic radiographs and lateral cephalograms of 615 subjects (300 males and 315 females) of ages ranging 9-18 years, and estimates of dental maturity (DI) and skeletal maturity [cervical vertebrae maturation indicators (CVMI)] were made. RESULTS: A highly significant association (r = 0.81 for males and r = 0.72 for females) was found between DI and CVMI. DI Stage B corresponded to Stage 2 of CVMI (prepeak of pubertal growth spurt) in both sexes. In males, DI stages C and D represent the peak of the pubertal growth spurt. In females, stages B and C show that the peak of the pubertal growth spurt has not been passed. DI stage E in females and DI Stage F in males correlate that the peak of the pubertal growth spurt has been passed. CONCLUSION: A highly significant association exists between DI and CVMI. Mandibular third molar DI stages are reliable adjunctive indicators of skeletal maturity.